2016
DOI: 10.1002/2016ja022477
|View full text |Cite
|
Sign up to set email alerts
|

Ion cyclotron instability at Io: Hybrid simulation results compared to in situ observations

Abstract: We present analysis of global three‐dimensional hybrid simulations of Io's interaction with Jovian magnetospheric plasma. We apply a single‐species model with simplified neutral‐plasma chemistry and downscale Io in order to resolve the ion kinetic scales. We consider charge exchange, electron impact ionization, and photoionization by using variable rates of these processes to investigate their impact. Our results are in a good qualitative agreement with the in situ magnetic field measurements for five Galileo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Results from the multispecies hybrid simulations exhibit significant improvement over those obtained from the single‐species simulations used before by Šebek et al (). The main improvements in the multispecies simulation model were inclusion of multiple plasma and neutral species in the environment and modified treatment of electron impact ionization.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Results from the multispecies hybrid simulations exhibit significant improvement over those obtained from the single‐species simulations used before by Šebek et al (). The main improvements in the multispecies simulation model were inclusion of multiple plasma and neutral species in the environment and modified treatment of electron impact ionization.…”
Section: Discussionmentioning
confidence: 63%
“…The unitary plasma density n e is represented by 100 macroparticles of singly ionized ion species or 50 macroparticles of the doubly ionized sulfur. In our single‐species hybrid simulations (Šebek et al, ), we found that a value of resistivity η=0.050.1emμ0vnormalA02false/ωc0 in the Ohm's law resulted in artificial acceleration of ions in the Alfvén wings. For this reason we use a lower value of η=0.0050.1emμ0vnormalA02false/ωc0 in this model.…”
Section: Simulation Model and Performed Simulationsmentioning
confidence: 63%
See 3 more Smart Citations